2021
DOI: 10.3390/ijerph181910438
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Hesitancy in the Month Following the Start of the Vaccination Process

Abstract: The occurrence of the novel coronavirus has changed a series of aspects related to people’s everyday life, the negative effects being felt all around the world. In this context, the production of a vaccine in a short period of time has been of great importance. On the other hand, obtaining a vaccine in such a short time has increased vaccine hesitancy and has activated anti-vaccination speeches. In this context, the aim of the paper is to analyze the dynamics of public opinion on Twitter in the first month aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
60
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(65 citation statements)
references
References 46 publications
3
60
2
Order By: Relevance
“…As in many other aspects of our lives, social media has become one of the channels in which individuals from all over the world have met and exposed ideas related to personal life choices or have criticized/supported the policies taken by the governments [13][14][15]. Even in the case of mask-wearing, social media have offered the possibility to people located in different parts of the world, some of them in partial or total isolation, to virtually meet and exchange opinions related to mask-wearing in the context of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in many other aspects of our lives, social media has become one of the channels in which individuals from all over the world have met and exposed ideas related to personal life choices or have criticized/supported the policies taken by the governments [13][14][15]. Even in the case of mask-wearing, social media have offered the possibility to people located in different parts of the world, some of them in partial or total isolation, to virtually meet and exchange opinions related to mask-wearing in the context of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Knowing that some of the classification algorithms rely on the word frequency, the Term Frequency-nverse Document Frequency (TF-IDF) has been used for reducing the weight of the most frequent words, which, in general, contain little to no information [15].…”
mentioning
confidence: 99%
“…The authors studied the period between November 2020 and February 2021 and determined that the negative sentiment declined over time [35]. Similar periods of time were considered by Liu and Liu [36] and Cotfas et al [13,14] regarding English tweets. Liu and Liu [36] showed that the public sentiment on COVID-19 vaccines varied over time and depended on geographic location, and Cotfas et al [13,14] underlined that the general public interest in the vaccination process has presented spikes that can be connected with the major events presented in the media in the selected period.…”
Section: Literature Reviewmentioning
confidence: 85%
“…Regarding the general opinion related to the COVID-19 vaccine expressed on Twitter, the discussions have evolved over time from simple messages, such as "I refuse", "I don't", "Not in my veins" and "Please vaccinate" to more complicated and better-defended arguments for and against vaccination, some of them mentioning and quoting the opinions of well-known physicians and researchers [13,14]. As a result, the analysis of the messages posted on Twitter can bring new insights into the reasons behind people's decisions to take the COVID-19 vaccine, either the 1st, 2nd or 3rd dose.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of vaccine-related content available on social media platforms have been conducted in the world. Those analyses are based on data extracted from social media platforms and examine vaccine hesitancy, acceptance, sentiment and administrative burden [ 24 , 25 , 26 , 27 , 28 ]. Study data acquisition from Facebook and Twitter commonly relies on automated IT solutions offering data collection, monitoring and analysis [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%